Streptococcus thoraltensis Bacteremia: First Described Case as a Fever of Unknown Origin in Human - Nikolaos Petridis; Athanasia Apsemidou; Georgios Kalopitas; Georgios Pilianidis; Iakovos Avramidis (Case Reports in Infectious Diseases)
Streptococcus thoraltensis has mainly been reported to cause infections in animals. Its clinical significance as a human pathogen has not yet been fully elucidated and needs further investigation. We describe here a case of bacteremia attributed to S. thoraltensis in a 55-year-old female patient admitted to our department due to fever of unknown origin. To the best of our knowledge, this is the first reported case of S. thoraltensis bacteremia in a human and the first reported case of S. thoraltensis as a cause of fever of unknown origin in human.